The Circumgalactic Medium Traced by Mg ii Absorption with DESI: Dependence on Galaxy Stellar Mass, Star Formation Rate, and Azimuthal Angle - Zeyu Chen; Enci Wang; Hu Zou; Siwei Zou; Yang Gao; Huiyuan Wang; Haoran Yu; Cheng Jia; Haixin Li; Chengyu Ma; Yao Yao; Weiyu Ding; et al. (The Astrophysical Journal)
Understanding the circumgalactic medium (CGM) distribution of galaxies is the key to revealing the dynamical exchange of materials between galaxies and their surroundings. In this work, we use the DESI Early Data Release data set to investigate the cool CGM of galaxies (0.3 < z < 1.7) by stacking the spectra of background quasi-stellar objects to obtain the Mg ii absorption of foreground galaxies. The equivalent width of Mg ii absorption strongly correlates with stellar mass, with EW(Mg ii ) $\propto {M}_{* }^{0.5}$ for star-forming galaxies with $logM_{* }/M_{\odot }\lt 10$ , but is independent of mass for galaxies above this mass. At a given stellar mass, EW(Mg ii ) is larger for galaxies of higher star formation rate with an impact parameter less than 50 kpc, while showing little dependence on galaxy size. By studying the dependence on azimuthal angle, we find EW(Mg ii ) is strongest at the direction near the minor axis for star-forming galaxies with $logM_{* }/M_{\odot }\lt 10.0$ , while no dependence on azimuthal angle is seen for luminous red galaxies. This indicates that the outflow associated with star formation enhances the Mg ii absorption. However, for galaxies with $logM_{* }/M_{\odot }\gt 10.0$ , the EW(Mg ii ) at the minor axis is largely suppressed with respect to low-mass galaxies. This suggests that the competing processes, such as stellar feedback and gravity, play a key role in shaping the distribution of outflowing gas.